Fuzzy solutions for wave equation with fuzzy coefficient - Sanam.Parvizi (International Journal of Advanced Science and Technology, 2020)
In this study we investigate wave equation as classical model of partial differential equations (PDE) with uncertain parameters. Our approach is based on employing the concept of cross product of fuzzy numbers. Using this concept, we construct the triangular fuzzy solutions. Finally, we compare the uncertainty of the solutions